Effects of golf instructors’ professional certification levels on amateur golfers’ perception of instructor expertise, instructor credibility, and lesson participation intention: testing placebo and nocebo effects - Yang, Hye Jin; Yang, Ji-Hye; Jung, Si Cheol; Choi, Chulhwan; Bum, Chul-Ho (Frontiers in Psychology, 2024)
This study investigated the differences in amateur golfers' perceptions of instructor expertise, instructor credibility, and lesson participation intention depending on the golf instructor's certification level . This study also aimed tto investigate whether placebo and nocebo effects exist depending on the certification level. Accordingly, the study analyzed 153 amateur golfers with at least one year of playing experience, and the results were as follows: First, there was a difference in the perception of instructor expertise among amateur golfers depending on the golf instructor's certification level. Specifically, there were significant differences in perceived performance and teaching skills but no differences in personality and emphasis on basic principles. Second, the participants reported significant differences in their perceptions of instructor credibility depending on the instructor's certification level. Instructor credibility of the tournament professional group was the highest, whereas that of the amateur group was the lowest. Third, the results showed differences in lesson participation intention among amateur golfers depending on the instructor's certification level. Lesson participation intention was higher for semi-professional and tournament professional instructors than for amateur instructors. These results verified the presence of psychological biases, such as placebo/nocebo effects, that result in differences in the perception of instructor expertise, instructor credibility, and lesson participation intention depending on the certification level of instructors. Additionally, based on the data obtained from this study, further research is required to improve the performance of golf instructors and create an efficient teaching environment.